2005
DOI: 10.1088/0953-8984/17/28/005
|View full text |Cite
|
Sign up to set email alerts
|

Electron Raman scattering in asymmetrical multiple quantum wells

Abstract: Optical properties of asymmetrical multiple quantum wells for the construction of quantum cascade lasers are calculated, and expressions for the electronic states of asymmetrical multiple quantum wells are presented. The gain and differential cross-section for an electron Raman scattering process are obtained. Also, the emission spectra for several scattering configurations are discussed, and the corresponding selection rules for the processes involved are studied; an interpretation of the singularities found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…In the past decade, several researchers have studied the differential cross-section (DCS) for the electron Raman scattering (ERS) to explicate the experimental results [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. For example, ERS in asymmetrical multiple quantum wells (QWs) without [9] and with an external electric field [10], effect of built-in electric field on ERS in InGaN/ GaN coupled QWs [11], ERS in semiconductor quantum wire in an external magnetic field [12], ERS in cylindrical quantum wires [13], magnetic field effects on the ERS in coaxial cylindrical quantum well wires [14], one phonon-assisted electron Raman scattering in a wurtzite cylindrical quantum well wire [15], magnetic field effect on the ERS in a cylindrical quantum dot (QD) [16], effects of hydrogenic impurity and geometrical size on the ERS in single and multilayered spherical QDs [17], combined effects of hydrostatic pressure, temperature and external electric field on ERS in a parabolic disc-shaped QD [18] were presented by various authors. On the other hand, the wurtzite GaN-based heterostructures have attracted much attention recently due to their potential applications.…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, several researchers have studied the differential cross-section (DCS) for the electron Raman scattering (ERS) to explicate the experimental results [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. For example, ERS in asymmetrical multiple quantum wells (QWs) without [9] and with an external electric field [10], effect of built-in electric field on ERS in InGaN/ GaN coupled QWs [11], ERS in semiconductor quantum wire in an external magnetic field [12], ERS in cylindrical quantum wires [13], magnetic field effects on the ERS in coaxial cylindrical quantum well wires [14], one phonon-assisted electron Raman scattering in a wurtzite cylindrical quantum well wire [15], magnetic field effect on the ERS in a cylindrical quantum dot (QD) [16], effects of hydrogenic impurity and geometrical size on the ERS in single and multilayered spherical QDs [17], combined effects of hydrostatic pressure, temperature and external electric field on ERS in a parabolic disc-shaped QD [18] were presented by various authors. On the other hand, the wurtzite GaN-based heterostructures have attracted much attention recently due to their potential applications.…”
Section: Introductionmentioning
confidence: 99%
“…Analytical solutions for asymmetrical double and triple quantum-wells are possible only for unbiased sharp rectangular QWs [49]. We select discrete variable representation (DVR) as a numerical method [39,50] for our Math-CAD calculations of a stationary 1D Schrodinger equation for confined eigenstates.…”
Section: Methods Of Discrete Variable Representation (Dvr)mentioning
confidence: 99%
“…The effect of reduced dimensionality on the free carrier absorption and the selection rules for intersubband transition, have been discussed in Ref. [30], where it is shown that the electron Raman scattering can only take place in the confinement direction, then…”
Section: Raman Cross-section and Net Raman Gainmentioning
confidence: 99%